2012
DOI: 10.1091/mbc.e12-10-0715
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-dependent cofilin activation and increased retrograde actin flow drive 5-HT–dependent neurite outgrowth inAplysiabag cell neurons

Abstract: 5-HT promotes neurite growth via IP3-dependent Ca2+ release in neuronal growth cones. Outgrowth depends on increased rates of actin array treadmilling mediated by Ca2+-calcineurin–dependent cofilin activation. This mode of growth contrasts with substrate-dependent responses, for which retrograde actin flow and advance rates have been inversely correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 89 publications
7
54
0
Order By: Relevance
“…8), a finding consistent with other studies that showed an increase in actin retrograde flow downstream of cofilin activation (51,56,57). Decrease of endogenous CIN by siRNA did not reduce retrograde flow, which one could have expected with lower levels of active cofilin.…”
Section: Discussionsupporting
confidence: 87%
“…8), a finding consistent with other studies that showed an increase in actin retrograde flow downstream of cofilin activation (51,56,57). Decrease of endogenous CIN by siRNA did not reduce retrograde flow, which one could have expected with lower levels of active cofilin.…”
Section: Discussionsupporting
confidence: 87%
“…We thus measured the retrograde flow of activated PA-GFP-actin in lamellipodia before and after irradiation of cofilin-KR (Figure 4A). Consistent with other results showing that cofilin activation increases retrograde flow (Delorme et al ., 2007; Zhang et al ., 2012), we saw a marked increase in flow rate when cells were overexpressing constitutively active cofilin S3A , which was significantly reduced by ∼44% (56 ± 4.0 to 37 ± 3.5 nm/s) after CALI (Figure 4, B and C). In cells expressing either cofilin-KR or KR alone, no change was observed after CALI; there was a slight increase in retrograde flow speed after CALI of cofilin S3E -KR (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with a recent study demonstrating an essential role for ADF/cofilin in regulating retrograde flow in neurogenesis (Flynn et al ., 2012) and other studies showing an increase in retrograde flow downstream of cofilin activation (Delorme et al ., 2007; Zhang et al ., 2012). Of importance, the decrease in retrograde flow rate suggests that the increase of F-actin at the back of the lamellipodia actin network after cofilin CALI is not simply a result of more F-actin being moved backward but instead is caused by loss of filament disassembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microtubules (MTs) and actin microfilaments have been implicated in neurite outgrowth, with many studies focusing on the growth cone at the tip of the axon. Previous models suggest that the driving forces for neurite outgrowth are MT polymerization and the treadmilling of F-actin (1,2). However, other studies demonstrate that F-actin is dispensable to outgrowth and neurites extend even in the absence of F-actin (3)(4)(5).…”
mentioning
confidence: 99%